Corporate Purpose: Meaningful Change or Marketing Tool? - Langford, Rosemary Teele (Victoria University of Wellington Law Review, 2025)
Recent times have seen an explosion of interest in, and focus on, the concept of corporate purpose in a number of disciplines partly in response to shifts in societal expectations of companies and their directors. However, as outlined in this article, there are a number of challenges to meaningful outworking of corporate purpose in practical terms.